Pengaruh Harga Terhadap Penjualan Produk Motor Yamaha Mio Pada PT. Hasjrat Abadi Outlet Karombasan Manado - Neisia, Tembesi Citra; Kalangi, Johny A. F; Walangitan, Olivia (Sam Ratulangi University, 2018)
With the advancement of technology in this era of globalization, every company strives to always improve the quality of production and marketing management with the aim of maximizing the profits targeted by each company. To overcome the tight competition in marketing then one of the efforts undertaken by the company is to set a competitive pricing strategy so that sales increase the maximum. The right price and integrated can produce an effect to the customer to build relationship with the consumer so as to increase sales volume. This study uses quantitative method with the number of samples in this study are 84 consumers. Where researchers calculate the results of consumer responses on the questionnaire by using SPSS application version 21, so it can be known whether there is correlation and how much influence of price variables on sales of these products. The results of this study indicate that there is a positive influence of t count is greater than t-table (24,447> 1,993). Based on the results of research data that has been processed, it can be concluded that the effect of price on product sales are at a very strong correlation level of 0.879 or 87.9%, while 12.1% influenced by other variables not examined in this study. Keywords: Price, Product Sales